2017
DOI: 10.1016/j.suc.2017.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Acute Management of Traumatic Brain Injury

Abstract: Synopsis Traumatic brain injury (TBI) is a leading cause of death and disability in trauma patients. As the primary injury cannot be undone, management strategies must therefore focus on preventing secondary injury by avoiding hypotension and hypoxia and maintaining appropriate cerebral perfusion pressure (CPP), which is a surrogate for cerebral blood flow (CBF). Cerebral perfusion pressure can be maintained by increasing mean arterial pressure (MAP), decreasing intracranial pressure (ICP), or both. MAP can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
163
1
45

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 256 publications
(210 citation statements)
references
References 99 publications
1
163
1
45
Order By: Relevance
“…Based on this review, the authors concluded that SBP ranges from 120–150 mm Hg and MAP ranges from 85–110 mm Hg may be the thresholds to consider to improve functional outcomes. These higher SBP thresholds above 90 mm Hg have not been universally accepted, however, given the limited evidence to support such changes without clear functional outcome and mortality benefit …”
Section: Blood Pressure Control In Neurologic Emergenciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on this review, the authors concluded that SBP ranges from 120–150 mm Hg and MAP ranges from 85–110 mm Hg may be the thresholds to consider to improve functional outcomes. These higher SBP thresholds above 90 mm Hg have not been universally accepted, however, given the limited evidence to support such changes without clear functional outcome and mortality benefit …”
Section: Blood Pressure Control In Neurologic Emergenciesmentioning
confidence: 99%
“…These higher SBP thresholds above 90 mm Hg have not been universally accepted, however, given the limited evidence to support such changes without clear functional outcome and mortality benefit. 52 Hypotension is commonly associated with ASCI due to a variety of pathophysiologic reasons including hypovolemia due to trauma or level of injury to the spinal cord and subsequent nerve innervation potentially affected. Abundant data on a target BP threshold when managing patients with ASCI are lacking.…”
Section: Traumatic Brain and Spinal Cord Injurymentioning
confidence: 99%
“…Estudos mostram PAS inicial no local das ocorrências <90 mmHg (hipotensão) em 4% dos indivíduos tratados por serviço médico de emergência, e a saturação periférica de oxigênio (SpO 2 ) <90% (hipóxia) foi documentada em 19% dos pacientes (2,22,11,32) . (12,28,33,34) . O exame primário desses pacientes deve incluir:…”
Section: Lista De Siglaunclassified
“…Vias aéreas e proteção da coluna cervical: assegurar que a via aérea esteja permeável, a fim de manter a oxigenação e prevenir a disfunção ventilatória, pois hipóxia e pressão arterial de oxigênio (PaO 2 ) ≤60 mmHg estão associadas a mortalidade em pacientes com TCE e, portanto, devem ser evitadas e corrigidas rapidamente. Como pacientes com TCE podem apresentar fratura de vértebras, sua coluna deve estar estabilizada e imobilizada (12,28,33,34) . (12,28,33,34) .…”
Section: Atendimento Inicial Das Vítimas De Tceunclassified
See 1 more Smart Citation